Eicosanoids and other oxylipins in liver injury, inflammation and liver cancer development - Alba, Mario M.; Ebright, Brandon; Hua, Brittney; Slarve, Ielyzaveta; Zhou, Yiren; Jia, Yunyi; Louie, Stan G.; Stiles, Bangyan L. (Frontiers in Physiology, 2023)
Liver cancer is a malignancy developed from underlying liver disease that encompasses liver injury and metabolic disorders. The progression from these underlying liver disease to cancer is accompanied by chronic inflammatory conditions in which liver macrophages play important roles in orchestrating the inflammatory response. During this process, bioactive lipids produced by hepatocytes and macrophages mediate the inflammatory responses by acting as pro-inflammatory factors, as well as, playing roles in the resolution of inflammation conditions. Here, we review the literature discussing the roles of bioactive lipids in acute and chronic hepatic inflammation and progression to cancer.